Foliar nitrogen and phosphorus stoichiometry of three wetland plants distributed along an elevation gradient in Dongting Lake, China - Feng Li (Nature Portfolio, 2017)
Abstract We examined foliar nitrogen (N) and phosphorus (P) stoichiometry of 3 wetland plants (Phalaris arundinacea, Miscanthus sacchariflorus, and Carex brevicuspis) distributed along an elevation gradient in the Dongting Lake, China, and how this stoichiometry is related to soil physico-chemical characteristics, elevation, and flooding days. Plant and soil samples were collected from 3 lakeshore sites. Total N and P concentrations of plants and six physico-chemical characteristics of the soil were measured, in addition to the elevation and flooding days. P. arundinacea and M. sacchariflorus had higher total N and P concentrations than C. brevicuspis. The foliar N:P ratio decreased with increasing elevation, and only increased with increasing foliar total N concentration. Canonical correspondence analysis indicated that the foliar stoichiometry was primarily regulated by soil water content, followed by soil nutrient concentration. The foliar N and P stoichiometry of the 3 wetland plants was insignificantly correlated with soil total P concentration. However, foliar stoichiometric characteristics and soil total N concentration significantly differed among the 3 species. These results demonstrate that spatial variation of foliar stoichiometry in wetland plants exists along an elevation gradient, with this information being useful for the conservation and management of wetland plants in this lake.